Anatomical Variations of Bilateral Posterior Circulation and Anterior Cerebral Artery: Case Report and Literature Review - Vianna, Jonnathan; Tertulino, Franklin de Freitas; de Lima, Eduardo Martiniano (Brazilian Journal of Case Reports, 2025)
It is not uncommon to find anatomical variations in the Circle of Willis in healthy individuals. These variations are typically singular or, more rarely, dual, and by definition, would not cause symptoms in the patient. However, reports in the literature suggest that these so-called "arterial variations" may be associated with the development of aneurysms, hemorrhages, and cerebral abnormalities, as well as increasing the risk of vascular insufficiency and severe brain damage during thromboembolic events. We present the case of a 64-year-old woman with complaints of refractory headache, whose magnetic resonance angiography demonstrated the association of three anatomical variations: azygos anterior cerebral artery, true fetal origin posterior cerebral artery, and complete fetal origin posterior cerebral artery.